Endoscopic Fenestration of Posterior Fossa Arachnoid Cysts - Patricia Dastoli; Marcos Devanir Silva Costa; Jardel Mendonça Nicácio; Sergio Cavalheiro (Brazilian Society for Pediatric Neurosurgery, 2022)
Introduction: Posterior Fossa arachnoid cysts (PFAC) are rare lesions in the childhood. Owing to the wide variety of cystic malformations within the posterior cranial fossa, PFAC have long attracted the attention of pediatric neurosurgeons because they can produce not only neurological symptons but also behaviro and learning deficts, in addition  to presenting major surgical challenges. Surgical treatment is warranted in symptomatic patients. Nowadays, neuroendoscopic techniques have established themselves as the treatment of choice of these lesions. Patients and Methods:  We present four cases of symptomatic PFAC which were treated using endoscopic neurosurgery. Endoscopic approaches were defined by the presence of hydrocephalus,  and discussed in each case. Results : Two cases of quadrigeminal plate cysts,  predominantly occupying the infratentorial compartment , one case of supracerebellar cyst and one case of cerebellopontine angle  were treated with good results. However, one case of quadrigeminal plate cyst developed a communicating hydrocephalus, requiring placement of cyst-ventricle peritoneal shunt, guided by the neuroendoscope. Discussion and Conclusion : A literature review was performed.  The clinical features, the advantages and disadvantages of several surgical treatments are discussed. Symptomatic PFAC should be treated. The relatively good results using endoscopic fenestration  buttresses our use as a first-line surgery.